Strengthening the Character of Middle School Students Through the Implementation of Role-Playing Methods in Fantasy Text Lessons - Tia Hana Resmita; Sutji Muljani; Tri Mulyono (FKIP - Universitas Riau, 2026)
This study aims to describe implementation of role-playing methods using fantasy texts to strengthen students’ character and to identify the factors. The study employed a descriptive qualitative approach and was conducted at SMP Negeri 3 Paguyangan with two seventh-grade teachers and 60 students as the subjects selected through purposive sampling. Data were collected through interviews, observations, and documentation, then analyzed using data triangulation. Triangulation of sources and techniques was performed to ensure the validity of the research data based on the sources obtained. The results of the study indicate that the fantasy-text-based role-playing method, which utilizes stories of local wisdom, is capable of increasing student engagement in learning and strengthening character traits such as honesty, discipline, responsibility, cooperation, and self-confidence. The effectiveness of the method is demonstrated by a learning implementation rate of 88%, student activity levels of 89%, and positive student responses of 68%. Supporting factors include the availability of local stories and high student interest, while inhibiting factors include the relatively long time required, the need for thorough preparation, space limitations, and students’ shyness and lack of self-confidence. Role-playing methods based on local wisdom show potential as an alternative learning approach to strengthen the character of students.